Sociological Analysis of the Important Characters in Kevin Kwan’s Crazy Rich Asians - Gusti Ayu Made Rai Suarniti (RETORIKA: Jurnal Ilmu Bahasa, 2021)
This research is about the sociological problems of five important characters in Kevin Kwan’s Crazy Rich Asian. Rachel Chu is the main character in this story comes from the middle class society. She has a relationships with Nicholas Young who comes from the upper class society. They face a lot of problems especially from Nicholas’s family who doesn’t agree with their relationships. Different society influences the character of someone. That’s why this research is aimed to find out the types of social class and the influence of social class on the character that showed in the story. The data were collected by reading the novel thoroughly then using the note-taking technique before being identified based on the topic. The collected data were descriptively analyzed by using qualitative-descriptive method to classify the types of social class and the influence of social class on the character that found in this novel. Based on the result of the research, it is found that there are three kinds of social class in Kevin Kwan’s Crazy Rich Asian, those are: Upper class, Middle class and Working class. Rachel Chu who comes from the middle class society has a simple personality. She prefers to save her money for food though she is a lecturer in university rather than her boy friend, Nicholas Young who comes from the worthy family. Nick’s family are also live glamor in Singapore. They spend a lot of money for fashion and jewelry. It much different with Rachel’s mom ( Kerry Chu) who originally comes from working or lower class society. She fulfills her daughter alone and becomes a single parent because she has divorced with her husband when Rachel still child. This condition make Eleanor Young doesn’t agree with the relationships however the power of love between Nick and Rachel defeated everything. Finally, they become a couple.